VERBALIZATION OF CONCEPT MOTHER IN OLEKSII DOVHIY’S POETIC LANGUAGE - STROKAL, Oleksandr (Linguistic and Conceptual Worldviews, 2025)
Background. Human knowledge about the environment exists in human consciousness in the form of certain mental formations called concepts. The concept MOTHER in the poetic worldview of the lyrical hero forms a unique conceptual space, as it combines both numerous collective traditional ideas and an individual author’s interpretation of it. In the poetic language, the specified concept is implemented by actualizing of its signs by the semantic components of the lexeme "mother". Topicality. The lexemes that denote the semantic components of the lexeme "mother" act as a unique language material that reflects the collective experience of humanity and ethnicity. In a poetic text, such units are expressions of the author’s style. Purpose: to characterize the peculiarities of the linguistic explication of the concept MOTHER and related signs and realities on the basis of Oleksii Dovhiy’s poetic texts. Task: to consider the grammatical, semantic, stylistic, individual-author’s characteristics of using the language units denoting the concept MOTHER, its signs and images associated with them. Methods: general scientific methods (descriptive with analysis and synthesis, induction and deduction, classification and systematization); special linguistic methods (conceptual analysis, lingual and poetic analysis). Results. The article emphasizes the special role of verbalizers in the display of various types of signs of the concept MOTHER in the poetic text. On the basis of the language material, the most used actualizations of the corresponding signs represented by the semantic components of the lexeme "mother" were investigated. Explicative units of such components were analyzed according to their grammatical and semantic-stylistic features. It is stated in the study that the actualization of the concept MOTHER in author’s poetic language occurs due to the use of simple and complex noun units and their derivatives, as well as due to the introduction of lexemes, which in the context create artistic images associated with the corresponding semantic components. Conclusions. The author of the article substantiates the importance of using lexemes denoted the semantic components of the lexeme "mother" in the poetic text. The researcher emphasized the author’s manner of simultaneous actualization of several semantic components of the lexeme "mother", which allows the poet to more accurately convey the assessment and significance of the relevant realities in the worldview of the lyrical hero.